THE EFFECT OF COMMODITY PRICES, EXCHANGE RATES, INFLATION, FOREIGN DIRECT INVESTMENT, AND HUMAN RESOURCES ON THE ECONOMY OF THE ORGANIZATION OF ISLAMIC COOPERATION (OIC) COUNTRIES - Evi Aninatin Ni'matul Choiriyah; Ilmiawan Auwalin (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the effect of world commodity prices on agriculture, energy, fertilizer, metals and minerals, precious metals, inflation, exchange rate of the United States Dollar (USD), Foreign Direct Investment, human resources on economics of Organization of Islamic Cooperation (OIC) which is proxied in Gross Domestic Product (GDP) in the 2009-2018 period. In this study, there are two models regarding the human resources variable, namely total population and labor force. Random Effect Model (REM) is used in this study to examine the relationship of independent variables to the dependent variable, both partially and simultaneously. The findings of this study, both the first and second models show that commodity prices in the agriculture, fertilizer, metal and mineral sectors, Foreign Direct Investment, and inflation have a negative and significant effect on the GDP of the OIC countries. Meanwhile, commodity prices in the energy sector, precious metals, and the exchange rate of the United States Dollar (USD) have a positive and significant effect on the GDP of the OIC countries. As well as the human resources variable, both the population and the labor force also have a positive and significant effect on the GDP of the OIC countries. This paper can be considered for the government or related institutions and agencies in formulating policies or regulations to improve and maintain economic stability in each OIC member country.Keywords: Macroeconomics, World commodities prices, OIC, and GDP